AESTHETICS OF VOLFGANGS DĀRZIŅŠ IN HIS COGNITIONS AND WORK (Mūzikas akadēmijas raksti, 2024)
Volfgangs Dārziņš (1906–1962), son of the famous Latvian romantical composer Emīls Dārziņš, has principally expanded the stylistic spectrum of Latvian music in two directions. Firstly, he is one of our first representatives of neo-classicism. Secondly, the most outstanding works of Volfgangs Dārziņš are marked by new, non-traditional interpretation of folklore, which has sometimes been characterized as barbarian and is similar to the archaic, pagan layers of folk music typical for Béla Bartók and Igor Stravinsky. The emigration period of Dārziņš’ work is especially marked with intensive and fruitful stylistic revitalization. However, some early signs of these styles are noticeable already in the works of 30-ties (which still are generally dominated by the link to the styles of romanticism and impressionism), as well as in critiques of this period. In this article I would like to give a broader insight in the aesthetic views of Volfgangs Dārziņš, which are revealed both in his critiques and letters, and also help to conceive the intentions of several of his musical works.